Rationality verses irrationality in fixed dose combinations: at a tertiary teaching hospital of rural Chhattisgarh, India - Tabish, Ahmed; Khan, Tanveer A.; N. B., Chandel; Anand, Rao; Chandresh, Mishra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Rational drug prescribing can be defined as appropriate drugs prescribed in the right dose, at correct time intervals and for a sufficient duration. Irrational drug use is a common problem in many countries of the world. Methods: A prospective observational study was conducted, total 300 patients attending various outpatient departments of tertiary health care rural hospital in Rajnandgaon district were interviewed and their prescriptions were analysed. Results: Total 350 drugs were prescribed 60 (17.14%) were prescribed by generic name and the rest 290 (82.86%) were prescribed by brand name. Only 18 (5.14%) drugs were not prescribed from hospital formulary. 264 (75.43%) drugs were dispensed from hospital pharmacy. On the basis of rationality score 53% prescriptions were rational, 30% semi rational and 17% irrational. Conclusions: In a rural hospital, where hospital formulary is based on WHO Essential medicine list, hundred percent utilization of hospital pharmacy service doctors and patients would ensure rational prescribing benefits of the patients coming from rural and uneducated background.